2014
DOI: 10.5901/mjss.2014.v5n4p543
|View full text |Cite
|
Sign up to set email alerts
|

Application of Grounded Theory in Career Research Reviewed

Abstract: Most research studies pose some element of concern, discrepancies and controversy. Grounded theory (GT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…In our mixed research design, the literature review of the theory development of GT plays a major role in bridging qualitative and quantitative studies. However, utilizing a literature review of GT is a debatable issue among many scholars (Van Rensburg and Ukpere, 2014). For those arguing for the use of a literature review in GT, there is also no agreement on where to place the literature review during the GT research process.…”
Section: Qualitative Design and Data Analysis (Phase I)mentioning
confidence: 99%
See 2 more Smart Citations
“…In our mixed research design, the literature review of the theory development of GT plays a major role in bridging qualitative and quantitative studies. However, utilizing a literature review of GT is a debatable issue among many scholars (Van Rensburg and Ukpere, 2014). For those arguing for the use of a literature review in GT, there is also no agreement on where to place the literature review during the GT research process.…”
Section: Qualitative Design and Data Analysis (Phase I)mentioning
confidence: 99%
“…For those arguing for the use of a literature review in GT, there is also no agreement on where to place the literature review during the GT research process. Van Rensburg and Ukpere (2014) discussed different views about this issue. In choosing the research process of GT to support our use of mixed research method when relating the qualitative research results to the quantitative study, this paper adopts the guidelines suggested by Pandit (1996).…”
Section: Qualitative Design and Data Analysis (Phase I)mentioning
confidence: 99%
See 1 more Smart Citation